Erythrodermic psoriasis and palmoplantar hyperkeratosis successfully treated with secukinumab: a case report - Martino Carriero (AboutScience Srl, 2022)
Erythrodermic psoriasis (EP) is a rare and severe form of psoriasis that affects 1 to 2.25% of patients, increasing mortality risk. To date, very few therapies have been approved for the treatment of this condition. Recently, biological therapies which specifically target inflammatory cytokines have improved the management and treatment of EP. Secukinumab, a human monoclonal antibody that specifically targets interleukin-17A (IL-17A), has been shown to be beneficial in different psoriasis settings. We report the case of a 72-year-old man affected by persistent EP and severe palmoplantar hyperkeratosis whose condition was not resolved after two rounds of treatment with prednisone and therapy with cyclosporine. Treatment with secukinumab significantly improved the symptoms of palmoplantar hyperkeratosis as early as the first weeks, with a decrease of Psoriasis Area Severity Index (PASI) score from 60 to 10, showing almost complete remission after 1 month. Consistent with the current literature, secukinumab treatment showed promising and encouraging clinical outcomes in the treatment of the patient's EP. However, more studies are needed to clarify the IL-17-dependent mechanism in the pathophysiology of EP.